Testing the bounds of compassion in young children. Issue 2 (15th February 2023) - Kirby, James N.; Kirkland, Kelly; Wilks, Matti; Green, Mitchell; Tanjitpiyanond, Porntida; Chowdhury, Nafisa; Nielsen, Mark
Abstract : Extensive research shows that, under the right circumstances, children are highly prosocial. Extending an already published paradigm, we aimed here to determine what factors might facilitate and inhibit compassionate behaviour. Across five experiments ( N = 285), we provide new insight into the bounds of 4- to 5-year-old children's compassionate behaviour. In the first three experiments, we varied cost of compassion by changing the reward (Study 1), using explicit instructions (Study 2) and ownership (Study 3). In the final two experiments, we varied the target of the compassionate behaviour, examining adults compared with puppet targets (Study 4), and whether the target was an in-group member (Study 5). We found strong evidence that cost reduces compassionate responding. By contrast, the recipient of compassion did not appear to influence responding: children were equally likely to help a human adult and a puppet, and an in-group member and neutral agent. These findings demonstrate that for young children, personal cost appears to be a greater inhibitor to compassionate responding than who compassion is directed toward.